2022
DOI: 10.1002/ecy.3647
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific plant‐mediated effects between herbivores converge at high damage intensity

Abstract: Plants are often exposed to multiple herbivores and densities of these attackers (or corresponding damage intensities) often fluctuate greatly in the field. Plant-mediated interactions vary among herbivore species and with changing feeding intensity, but little is known about how herbivore identity and density interact to determine plant responses and herbivore fitness. Here, we investigated this question using Triadica sebifera (tallow) and two common and abundant specialist insect herbivores, Bikasha collari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…Future research should investigate changes in other aspects of larval performance as well, such as rate of development or growth over longer periods of time. Additionally, recent evidence from Chinese tallow showed aboveground herbivore effects on belowground root nutrient content, as well as herbivore performance, were dependent on the identity and density of aboveground herbivores (Wan et al, 2022). Future research should investigate different densities of aboveground striped cucumber beetles and squash bugs to discern if there are any densitydependent effects on belowground striped cucumber beetle larval performance.…”
Section: Discussionmentioning
confidence: 98%
“…Future research should investigate changes in other aspects of larval performance as well, such as rate of development or growth over longer periods of time. Additionally, recent evidence from Chinese tallow showed aboveground herbivore effects on belowground root nutrient content, as well as herbivore performance, were dependent on the identity and density of aboveground herbivores (Wan et al, 2022). Future research should investigate different densities of aboveground striped cucumber beetles and squash bugs to discern if there are any densitydependent effects on belowground striped cucumber beetle larval performance.…”
Section: Discussionmentioning
confidence: 98%
“…For example, a common garden survey found that different non-native species suffered from 0% to more than 40% leaf herbivory from generalists (Agrawal & Kotanen, 2003). Variation in herbivore pressure should lead to variation in defense traits (Coverdale & Agrawal, 2022;Wan et al, 2022) and less intense and less frequent herbivory is theorized to select for allocation to induced defenses (Bixenmann et al, 2016). However, how this variation in generalist herbivore pressure affects any potential tradeoffs in constitutivevs.…”
Section: Introductionmentioning
confidence: 99%
“…Different non‐native species often experience very different degrees of generalist herbivore pressure (Agrawal & Kotanen, 2003; Sims‐Chilton et al, 2009). Such variation in herbivore pressure should lead to variation in defence traits (Coverdale & Agrawal, 2022; Wan et al, 2022) and less intense and frequent herbivory should select for allocation to induced defences (Bixenmann et al, 2016). However, how this variation in generalist herbivore pressure affects potential trade‐offs in constitutive versus induced defensive strategies among non‐native species is unknown.…”
Section: Introductionmentioning
confidence: 99%